2022
DOI: 10.3390/agronomy12123001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Allelopathic Activity Interactions of Some Medicinal Plants Using Fractional Inhibitory Concentration and Isobologram

Abstract: Allelopathy is a physiological process with an ecological concept and application. Allelopathy is the result of the production of biologically active molecules by growing plants or their remains, which may have a direct effect on the growth and development of individuals of the same species or other species after changing their shape and entering the environment. As regards, the use of natural compounds in the control of weeds and pests is a priority. In this research, the allelopathic activity of 123 specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Scientists of the Ferdowsi University of Mashhad Crop Research Center and Mashhad Botanical Garden (S. Sadeqifard et al, 2022) collected different parts of plants -flowers, stems, leaves, roots (123 samples) belonging to 31 families of medicinal plants. The influence of the studied plants on the basal and hypocotyl growth of lettuce seeds, comparison with the control in different plant families was studied separately.…”
Section: Resultsmentioning
confidence: 99%
“…Scientists of the Ferdowsi University of Mashhad Crop Research Center and Mashhad Botanical Garden (S. Sadeqifard et al, 2022) collected different parts of plants -flowers, stems, leaves, roots (123 samples) belonging to 31 families of medicinal plants. The influence of the studied plants on the basal and hypocotyl growth of lettuce seeds, comparison with the control in different plant families was studied separately.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, Origanum EOs can be considered as alternative bioherbicides for the weeds tested in different crops. In the next study [22], the allelopathic activity of 123 MAPs from 31 families was analyzed using the dish-pack method on a lettuce seed model. Their allelopathic interaction effects were examined after selecting the most potent inhibitory compounds.…”
Section: Yield and Quality Of Aromatic Plantmentioning
confidence: 99%
“…Ukrainian Black Sea Region Agrarian Science, 26 (4), [19][20][21][22][23][24][25][26][27][28][29] According to M. Shinwari et al (2013), 70 species of Japanese plants were examined for allelopathy using the aqueous extraction method. The scientists concluded that before large-scale cultivation of any medicinal plant in an established agricultural field, the plant should be evaluated allelopathically, as chemical exposure from previous plants, residues, related plants and even autotoxicity can adversely affect the cropping system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ukrainian Black Sea Region Agrarian Science, 226 (4), [19][20][21][22][23][24][25][26][27][28][29] Алелопатична активність рослин Hyssopus officinalis L. Анотація. Необхідність у фітомеліорації спонукає на введення у культуру рослин, які не тільки будуть мати декілька напрямків використання отриманої сировини, але й сприяти оздоровленню ґрунтів та бути добрим попередником для подальшого успішного вирощування наступних за ними сільськогосподарських культур.…”
Section: Conflict Of Interestunclassified
See 1 more Smart Citation